The Influence of STEAM-Integrated Project-Based Science Learning Viewed from Scientific Attitudes on Student Creativity - Ramdhani Sucilestari; Kurniawan Arizona; Lalu Ahmad Didik Meiliyadi; Masiah Masiah; Rendi Restiana Sukardi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study aims to explore the impact of integrated STEAM-based project-based science learning, considering scientific attitudes, on students' creativity. Despite a growing body of literature supporting the benefits of STEAM, few studies have examined the interaction between scientific attitudes and creativity in project-based learning contexts. This research uses a quantitative approach with a factorial experimental design, including two main factors: class type (experimental vs. control) and scientific attitude (high vs. low). The sample consists of 74 students from the PGMI FTK UIN Mataram study program, who were randomly assigned to experimental and control groups. Data collection involved pretests and posttests to measure creativity, alongside scientific attitude questionnaires. Descriptive and inferential statistics, including two-way ANOVA, were used to analyze the data. The results show that the experimental group participating in STEAM-based project learning exhibited a significant increase in creativity (p=0.000; partial η² = .681) compared to the control group. Scientific attitude also had a significant effect on creativity (p=0.000; partial η² = .165). However, no interaction effect between class type and scientific attitude on creativity was found (p=0.925). These findings suggest that both STEAM-based project learning and scientific attitude independently contribute to enhancing creativity. This study provides new insights by addressing the gap in research concerning the role of scientific attitudes in project-based STEAM learning. It also highlights the potential for designing science curricula that integrate both innovative teaching methods and the fostering of positive scientific attitudes to enhance student creativity.